Potential markers of cancer stem-like cells in ESCC: a review of the current knowledge - Wang, Lu; Liu, Huijuan; Liu, Yiqian; Guo, Shixing; Yan, Zhenpeng; Chen, Guohui; Wu, Qinglu; Xu, Songrui; Zhou, Qichao; Liu, Lili; Peng, Meilan; Cheng, Xiaolong; et al. (Frontiers in Oncology, 2024)
ESCC is the principal histological type in China, which has the highest incidence and mortality compared with other countries(1). Despite advances in treatment method, patient survival rates have not obviously improved, which often leading to treatment resistance and tumor recurrence. In ESCC have special cells called cancer stem cells (CSCs), CSCs capable of self-renewal and differentiation ability, which reflect the development process and prognosis of cancer. In this review, we evaluated that cancer stem cells (CSCs) which are identified from the expression of cell surface markers in esophageal squamous cell carcinoma (ESCC). By inducing EMT to participate in tumor migration and invasion, stem cells promote tumor redifferentiation. Some factors can inhibit the migration and invasion of esophageal squamous cells through the EMT-related pathway. We here summarize the research progress on the surface markers of CSCs, EMT pathway, and microenvironment in the process of tumor growth. Thus, these data may be more valuable for clinical application.